Symbolic representation of Tun Dr Mahathir: visual analysis of a Malaysian short film - Uma Rani A Rethina Velu; How, Cherish (Penerbit Universiti Kebangsaan Malaysia, 2019)
The fragmented frames of a short film which comprise still images and signs can be visually explored in the representation of timing. The significance of such a visual representation can lead to the formation of synchronised discursive structures that reflect upon political and social time summons in the past, present and future. The issue is that the political and social agendas mapped with ideas of a pre-election campaign and synchronised with time summons may indirectly provoke viewers’ perception of a social actor through semiotic implications. Using a single component framework consisting of Kress and van Leeuwen’s (2006) grammar of visual design, representational and viewer network and Hall’s (2006) reception theory, this study explores the way agency is targeted visually towards the idea of a political change with pre-election sentiments of a prime minister. On one hand, through the choice of images Tun Dr Mahathir’s past political successes are symbolically represented. On the other hand, he is signified with message of ‘hope’ for a better future to his country and nation.